The Mass Infection of COVID-19 in Daegu City of Korea: Vascular Surgeons’ Perspective - Roh, Young-Nam (Vasc Specialist Int, 2020)
Since February 18, 2020, the number of patients with COVID-19 has increased rapidly after the infection was initially confirmed in Daegu. Daegu city subsequently became the largest epicenter of the coronavirus outside China. In the early days of the outbreak of mass infection, Daegu citizens were in various difficult circumstances. Vascular surgery in Daegu was also affected as much as other medical field. Most of elective schedule were canceled, and the vascular surgeons cooperated to utilize the limited medical resources in Daegu region. Fortunately, the citizens of Daegu city could overcome the first crisis because of matured citizenship, sufficient medical resources and the timely-supplied surplus bed for patient isolation. Now all humanity today is interdependent and we are all one community in the pandemic. To overcome pandemic, it is necessary to respect and share experiences in various places at the beginning of the crisis.